2021
DOI: 10.1002/cam4.4258
|View full text |Cite
|
Sign up to set email alerts
|

National trends and survival outcomes of penile squamous cell carcinoma based on human papillomavirus status

Abstract: Background: There are no series evaluating penile squamous cell carcinoma (pSCC) based on human papillomavirus (HPV) infection. Herein, we present national registry data on clinical and survival outcomes for pSCC based on HPV status. Methods:We performed a retrospective review of 1224 pSCC patients with known HPV staining from the National Cancer Database. Patients with cM1 disease, those who did not receive treatment, or had missing follow-up data were excluded. Logistic regression identified factors associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…1 However, unlike other anatomic sites with HPV-associated and HPV-independent cancers, in which the former have consistently shown to have a better prognosis than the latter, 7 it is still unclear whether this prognostic implication also applies to PSCC. 8,9 Recently, a few studies have shown a trend towards longer disease-free survival in patients with HPV-associated PSCC. 10,11 Similar to vulvar squamous cell carcinomas, 12 the majority of PSCC develop from premalignant lesions generically named penile intraepithelial neoplasia (PeIN).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, unlike other anatomic sites with HPV-associated and HPV-independent cancers, in which the former have consistently shown to have a better prognosis than the latter, 7 it is still unclear whether this prognostic implication also applies to PSCC. 8,9 Recently, a few studies have shown a trend towards longer disease-free survival in patients with HPV-associated PSCC. 10,11 Similar to vulvar squamous cell carcinomas, 12 the majority of PSCC develop from premalignant lesions generically named penile intraepithelial neoplasia (PeIN).…”
mentioning
confidence: 99%
“…Significant epidemiological differences have been identified between these 2 main types of PSCC, with HPV-associated neoplasms usually arising in men with a history of smoking habit and multiple sexual partners,6 while the HPV-independent tumors are frequently associated with chronic inflammatory conditions, lichen sclerosus, and phimosis 1. However, unlike other anatomic sites with HPV-associated and HPV-independent cancers, in which the former have consistently shown to have a better prognosis than the latter,7 it is still unclear whether this prognostic implication also applies to PSCC 8,9. Recently, a few studies have shown a trend towards longer disease-free survival in patients with HPV-associated PSCC 10,11…”
mentioning
confidence: 99%
“…Nonetheless, data concerning anal SCC is equivocal, and discrepancies might be detected around the world [ 12 , 13 ]. However, the incidence of anal SCC has increased in PLWH over the last few years, although future projections suggest these figures are stabilizing [ 13 , 14 , 15 ]. Conversely, an increase in the incidence of HPV-driven oropharyngeal SCC is predicted in the coming years [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, an increase in the incidence of HPV-driven oropharyngeal SCC is predicted in the coming years [ 16 ]. Vulvar, vaginal, and penile SCC are less common than cervical or anal SCC, and disparity data are available for these diseases [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in Japan, the age-adjusted incidence of PSCC was reportedly 0.2 per 100,000 men in a population-based study of PC from 15 Japanese selected cancer registries [ 4 ]. The etiology of PSCC is multifactorial with risk factors such as smoking, chronic inflammation, balanitis, history of phimosis, poor hygiene, socioeconomic status, and human papilloma virus (HPV) infection, particularly types 16 and 18 [ 3 , 5 , 6 ]. Lymph node metastasis (LNM) at initial diagnosis is the most important prognostic marker [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%